Trends in Landings by Trawls of Five Designs off Veraval Coast - putra, Pravin; M.P., Remesan; R.S., Manoharadoss (Fishery Technology, 2025)
Variations in the composition of fish landed by demersal trawls of five different designs during the period of 1988-1993 off Veraval coast are reported in this paper. The average catch/h was 48.53 kg for the entire period. The catch rate was maximum (58.46 kg/h) during 1988-89 and it declined to 28.73 kg/h in the year 1992-93. The catch was dominated by ribbon fish (17%), cephalopods (8.7%) and sciaenids (12.9%) during the period. There was no significant difference in the catch rate of individual species in depth ranges of 20-30 and 31-40 m.